The Effect of Sleep Deprivation on Ocular Vestibular Evoked Myogenic Potentials Using Air Conducted Sound. (21st January 2014) - Xie, Su-Jiang; Bi, Hong-Zhe; Yao, Qin
Abstract : Vestibular evoked myogenic potential (VEMP) in response to a loud air conducted sound (ACS) recorded from extraocular muscles, the so-called ocular VEMP (oVEMP), has been confirmed to be able to evaluate utricular function. This study aimed to evaluate the effect of sleep deprivation (SD) on oVEMP parameters. oVEMPs were recorded in 20 male healthy subjects once after an ordinary sleep and once after 26–29 h of SD. The latencies of peak N1 and P1, N1-P1 amplitude, N1-P1 interval, and asymmetry ratio (AR) of oVEMP recorded from both eyes under normal sleep and SD conditions were 10.04 ± 0.59 ms versus 10.56 ± 0.69 ms (left eye), 14.95 ± 0.92 ms versus 15.64 ± 1.05 ms (left eye), and 7.44 ± 2.86  µ V versus 5.26 ± 2.15  µ V (left eye); 10.08 ± 0.66 ms versus 10.64 ± 0.73 ms (right eye), 14.88 ± 0.89 ms versus 15.59 ± 1.02 ms (right eye), and 7.16 ± 2.88  µ V versus 5.04 ± 2.05  µ V(right eye); 10.40 ± 5.81% versus 11.43 ± 6.37%, respectively. After SD, the latencies of oVEMP were delayed and N1-P1 amplitude was lower, whereas N1-P1 interval and AR remained unchanged. The present study showed that oVEMP test could be used to evaluate the fatigue induced by SD.